Supply chain resilience as a mediator of the relationship between entrepreneurial marketing and competitive advantage in service-sector SMEs in Thailand: Evidence from the Nakhonchaiburin region - Phusamphao, Nantaphon; Suvittawat, Adisak (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate how supply chain resilience (SCR) mediates the relationship between entrepreneurial marketing (EM) and competitive advantage (CA) among service-sector small and medium-sized enterprises (SMEs) in Thailand, grounded in the resource-based view (RBV) and dynamic capabilities theory (DCT). A quantitative research design was adopted, using a structured questionnaire distributed to 393 SME entrepreneurs and managers in the Nakhonchaiburin region through a multi-stage sampling technique. Data were analyzed using structural equation modeling (SEM) via SPSS and AMOS to test the proposed hypotheses and model fit. The findings revealed that EM exerted a statistically significant positive direct influence on both CA and SCR, while SCR also positively influenced CA and partially mediated the EM–CA relationship. The results suggest that service-sector SMEs in Thailand that adopt EM practices such as proactive innovation, customer-centric risk management, value network creation, and opportunistic resource leveraging enhance their resilience and sustain competitiveness in turbulent environments. The study concludes that integrating EM and SCR as complementary dynamic capabilities and strategic resources is essential for maintaining long-term CA. Practically, the findings provide strategic guidance for SME managers, policymakers, and practitioners to collaboratively develop EM and SCR competencies that strengthen firm- and sector-level resilience.